Experimental Study on Diesel Spray Characteristics and Autoignition Process - Taşkiran, Özgür Oğuz; Ergeneman, Metin (Wiley, 2011)
The main goal of this study is to get the temporal and spatial spray evolution under diesel‐like conditions and to investigate autoignition process of sprays which are injected from different nozzle geometries. A constant volume combustion chamber was manufactured and heated internally up to 825 K at 3.5 MPa for experiments. Macroscopic properties of diesel spray were recorded via a high‐speed CCD camera by using shadowgraphy technique, and the images were analyzed by using a digital image processing program. To investigate the influence of nozzle geometry, 4 different types of divergent, straight, straight‐rounded, convergent‐rounded nozzles, were manufactured and used in both spray evolution and autoignition experiments. The internal geometry of the injector nozzles were obtained by using silicone mold method. The macroscopic properties of the nozzles are presented in the study. Ignition behaviour of different nozzle types was observed in terms of ignition delay time and ignition location. A commercial Diesel fuel, n‐heptane, and a mixture of hexadecane‐heptamethylnonane (CN65—cetane number 65) were used as fuels at ignition experiments. The similar macroscopic properties of different nozzles were searched for observing ignition time and ignition location differences. Though spray and ignition characteristics revealed very similar results, the dissimilarities are presented in the study.
Keywords: QC251-338.5; Heat